VISUALIZATION OF MEDICAL IMAGES - Bahramov Rustam Rakhmatullaevich; Yusupova Zilola Islombekovna, Odilov Kahramon Ergashevich, Ortikova Feruza Anvar qizi, Shukurov Axro (Researchparks Publishing, 2023)
The role of medical images in medicine has become increasingly important in recent years. Accurate diagnosis for patients is of great importance in today's world. The modern methods of treatment, diagnostic methods, early detection and prevention of diseases, and the promptness of the first aid provided to the patient by healthcare professionals are all related to the accuracy of medical images. The ambiguity of images can lead to incorrect diagnosis of the patient.